Liquefaction of dried distiller's grains with solubles (DDGS) followed by hydroprocessing to produce liquid hydrocarbons. (15th June 2015) - Tanneru, Sathish K.; Steele, Philip H.
Highlights: Conversion of DDGS to value-added liquid hydrocarbons was performed successfully. Hydroprocessing of HTL product was more successful compared to the pyrolysis oil. The HHV of hydrocarbons produced increased by 127.2% as compared to DDGS. Abstract: Dried distiller's grains with solubles (DDGS) is a byproduct of corn ethanol production in distillery industries. Presently the main use of DDGS is as livestock feed due to its high protein content. The demands for production of transportation fuel ethanol are increasing due to the increased Renewable Fuels Standard 2 (RFS2) mandate for higher ethanol production. Simultaneously DDGS supply as a co-product is also necessarily markedly increasing. There is a potential for DDGS supply to outgrow the demand for livestock feed or the increased supply has the potential to drive prices down. Therefore, it is highly desirable to find alternative uses of DDGS as a renewable source in the production of fuels or value-added chemicals. The objective of this study was to produce transportation fuel range hydrocarbons from DDGS feedstock. In this study, DDGS was liquefied followed by hydroprocessing of the liquefied DDGS product to produce a hydrocarbon mixture. In the first step, liquefaction of DDGS was performed in a liquid media in the presence of a base catalyst at a temperature in the range of 400 °C. In the second step, the liquefied DDGS product was hydroprocessed in the presence of a heterogeneous catalyst at a temperature of 425 °C under pressurized hydrogen at 1500 psig. The physical and chemical properties of the liquefied DDGS product and the hydrocarbon mixture were measured by using American Society of Testing Methods. The hydrocarbons produced were analyzed by gas chromatography–mass spectroscopy, detailed hydrocarbon analysis, Fourier transform infrared spectroscopy, simulated distillation analysis and elemental analysis.